Al-Madaih An-Nabawiyyah: Its Literary History and Transformational Functions in the 21st Century Era - Maimunah, Iffat; Wargadinata, Wildana; Bahruddin, Uril; Ibrahim, Faisal Mahmoud Adam (Journal of Al-Tamaddun, 2023)
From an Islamic perspective, al-madaih an-nabawiyyah (praise of the Prophet Muhammad PBUH) is a part of Islamic literature that plays a central role in various aspects of life. This study aimed to investigate the literature, history, and functional diversity of al-madaih an-nabawiyyah in the 21st century. This study adopted Swingewood and Laurenson’s sociological approach. Data were obtained through references to literary history studies, observations and interviews. Observations focused on the functional diversity of al-madaih an-nabawiyah, while interviews were conducted with al-madaih an-nabawiyah figures and activists who were met at the activity center. In addition to these methods, data was also obtained from documents related to the existence and activities of congregations which have made reading al-madaih an-nabawiyah have a transformational function in the 21st century era. This paper shows that the emergence of al-madaih an-nabawiyyah literature was influenced by the rise of Muslim religious fanaticism, which encouraged love and longing for noble figures, and the encouragement of Muslims to eliminate life’s anxieties by asking for spiritual intercession from the Prophet Muhammad PBUH. Another factor that underlies the development of al-madaih an-nabawiyyah literature is the development of tasawuf tendencies and ascetic life (zuhd) among Muslims. This paper shows that the literary theme of al-madaih an-nabawiyyah includes the Prophet’s majesty and the Muslims’ religiosity by imitating by imitating the Prophet’s wisdom and glory. Apart from being a monumental literary work, al-Madaih an-Nabawiyyah has undergone a shift present generation’s needs, as a prayer and worship to improve the quality of life, piety, soothe the soul, as well as an expression of longing and love for the Prophet Muhammad PBUH. Reading al-madaih an-nabawiyyah has become a social, economic, cultural and political activity. Many Muslims used al-madaih an-nabawiyyah reading program as a medium to strengthen friendship or create an atmosphere of harmony in the people. This paper stressed the need for further studies on the development of al-madaih an-nabawiyyah literature as a complete literary work which is a masterpiece that accompanies Muslims’ lives.